2000
DOI: 10.1053/euhj.1999.2039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intravenously administered dofetilide versus amiodarone in the acute termination of atrial fibrillation and flutter. A multicentre, randomized, double-blind, placebo-controlled study

Abstract: Intravenous dofetilide is significantly more effective than amiodarone or placebo in restoring sinus rhythm in patients with atrial fibrillation or flutter. However, when infused intravenously at this dose and rate, dofetilide causes a significant incidence of torsade de pointes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 28 publications
2
55
0
1
Order By: Relevance
“…Galve et al found no significant difference in the conversion rate between placebo and 5 mg/kg amiodarone given as a 30-minute infusion followed by 1,200 mg over 24 h [10]. Bianconi found no significant difference in conversion to sinus rhythm between placebo and 5 mg/kg amiodarone given as a 15-minutes infusion [29]. Martínez-Marcos compared amiodarone with flecainide and propafenone and observed a significantly lower conversion rate in patients treated with amiodarone given as a 5 mg/kg infusion in 20 minutes [30].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Galve et al found no significant difference in the conversion rate between placebo and 5 mg/kg amiodarone given as a 30-minute infusion followed by 1,200 mg over 24 h [10]. Bianconi found no significant difference in conversion to sinus rhythm between placebo and 5 mg/kg amiodarone given as a 15-minutes infusion [29]. Martínez-Marcos compared amiodarone with flecainide and propafenone and observed a significantly lower conversion rate in patients treated with amiodarone given as a 5 mg/kg infusion in 20 minutes [30].…”
Section: Discussionmentioning
confidence: 95%
“…Martínez-Marcos observed symptomatic hypotension in 2 of 50 patients treated with amiodarone. In that study, symptomatic hypotension also occurred in 2 of 50 patients treated with flecainide, and 2 of 50 treated with propafenone, thus leaving the etiology of hypotension uncertain [29]. In a study comparing diltiazem with amiodarone, diltiazem had to be discontinued more often because of symptomatic hypotension [15].…”
Section: Side Effects Of Intravenous Amiodaronementioning
confidence: 97%
“…Conversion rates of amiodarnone of 48-87% have been reported in critically ill patients [6,18]. The efficacy of amiodarone in atrial flutter is lower than that in atrial fibrillation [19]. However, 13-52% of patients remain in atrial fibrillation or flutter.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have noted the rate of chemical cardioversion (CCV) to increase in a dose-dependent manner, the SAFIRE-D trial noted rates of 29.9% for 500 mcg BID, 9.8% for 250 mcg BID and 6.1% for 125 mcg BID [88,93]. Dofetilide has been noted to be more effective for CCV in AFL than AF with reported comparisons of 65% vs. 25% [95], and 75% vs. 22% [96].…”
Section: Dofetilidementioning
confidence: 99%